2015
DOI: 10.1016/j.appet.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational differences in beliefs about healthy eating among carers of left-behind children in rural China: A qualitative study

Abstract: China's internal migration has left 61 million rural children living apart from parents and usually being cared for by grandparents. This study aims to explore caregivers' beliefs about healthy eating for left-behind children (LBC) in rural China. Twenty-six children aged 6-12 (21 LBC and 5 non-LBC) and 32 caregivers (21 grandparents, 9 mothers, and 2 uncles/aunts) were recruited in one township in rural China. Children were encouraged to keep food diaries followed by in-depth interviews with caregivers. Disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
37
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
7
37
1
1
Order By: Relevance
“…Studies have found that left-behind children are more vulnerable to malnutrition compared to their counterparts from intact families [ 34 , 84 , 85 87 ]. Grandparents as caregivers often have poorer nutritional knowledge [ 88 ] and beliefs on healthy eating unflavoured for children’s nutritional development [ 89 ] than parental caregivers in rural China. Chinese evidence also shows that high rates of malnutrition among children are largely due to a lack of knowledge regarding healthy dietary intake rather than food shortages [ 7 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that left-behind children are more vulnerable to malnutrition compared to their counterparts from intact families [ 34 , 84 , 85 87 ]. Grandparents as caregivers often have poorer nutritional knowledge [ 88 ] and beliefs on healthy eating unflavoured for children’s nutritional development [ 89 ] than parental caregivers in rural China. Chinese evidence also shows that high rates of malnutrition among children are largely due to a lack of knowledge regarding healthy dietary intake rather than food shortages [ 7 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the price of meat and cooking oil contributed to the trend (Lu & Goldman, 2010;Wang, Zhai, Du, & Popkin, 2008). Because meat is still relatively expensive in China, families view consumption of meat as a status symbol and thus, consume more of it when their income rises (Zhang, Becares, Chandola, & Callery, 2015). Meanwhile, Chinese children consume most of their meals at home (approximately 91% in 1997), even though eating out has become more popular.…”
Section: The Potential Mechanisms and Heterogeneity Of The Maternal Ementioning
confidence: 99%
“…However, the average level of education of the parent/guardian of LBC was less than for non-LBC, and they may lack knowledge of nutrition. These caregivers tend to adopt a higher-calorie (higher-fat and carbohydrate) diet, eat fewer fruits and vegetables than recommended and may take the same approach to their children [7]. Guardians, particularly grandparents, may compensate or even overcompensate the children for the absence of their parents, for example, by offering children only the foods they like [35], thereby encouraging bad habits to develop.…”
Section: Discussionmentioning
confidence: 98%
“…Their guardians have been reported as worried about not having enough food and so have tended to emphasize the importance of starchy foods to improve growth, rather than a balanced diet [7]. LBC are therefore significantly more likely to become ill or develop chronic conditions than children living with their parents [8].…”
Section: Introductionmentioning
confidence: 99%